1994
DOI: 10.1073/pnas.91.3.1049
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity of seagrass populations using DNA fingerprinting: implications for population stability and management.

Abstract: Populations of the temperate seagrass, Zostera marina L. (eelgrass), often exist as discontinuous beds in estuaries, harbors, and bays where they can reproduce sexually or vegetatively through donal propagation. We examined the genetic structure of three geographically and morphologically distinct populations from central California (Elkhorn Slough, Tomales Bay, and Del Monte Beach), using multilocus restriction fragment length polymorphisms (DNA fingerprints Seagrasses form extensive meadows along the shore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(36 citation statements)
references
References 15 publications
0
35
1
Order By: Relevance
“…Amphibolis antarctica appears to be genetically analysis, the M13 fingerprinting method may be expected to reveal differences between individuals (Vassart et a!., 1987;Rogstad et at., 1988;Rogstad, 1993;Alberte et at., 1994). However, maternal parent and offspring plant tissue as well as several different seedlings from other parental shoots were tested but gave no detectable differences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphibolis antarctica appears to be genetically analysis, the M13 fingerprinting method may be expected to reveal differences between individuals (Vassart et a!., 1987;Rogstad et at., 1988;Rogstad, 1993;Alberte et at., 1994). However, maternal parent and offspring plant tissue as well as several different seedlings from other parental shoots were tested but gave no detectable differences.…”
Section: Resultsmentioning
confidence: 99%
“…Female-dominated sex ratios are often documented among apomicts and thus apomixis cannot be discounted among seagrasses, particularly where genetic variability is low (Richards, 1986;Les, 1988;Asker & Jerling, 1992). The few published studies of genetic variability in seagrass populations have led to conflicting generalizations about their genetic diversity and recruitment methods (McMillan, 1982(McMillan, , 1991Les, 1988;Fain et a!., 1992;Laushman, 1993;Alberte et a!., 1994;Waycott, 1995). Most of these studies have been conducted on monoecious and hermaphrodite seagrasses, principally the northern hemisphere species Zostera marina, using allozymes (Gagnon et a!., 1980;Laushman, 1993), RFLPs (Fain et a!., 1992) and DNA fingerprinting (Alberte et al, 1994).…”
mentioning
confidence: 99%
“…Species such as Ceratophyllum echinatum are predominantly clonal with little variation (Les, 1991), whereas others such as Zostera marina have genetically variable populations comprising many individuals (Laushman, 1993). Several other studies on hydrophiles have investigated the fine-scale genetic structure of populations, documenting both multiclonal (Les, 1991;Laushman, 1993;Alberte et at., 1994;Lokker et at., 1994;Waycott, 1995) and apparently uniclonal (Les, 1991; Correspondence and present address: Department of Tropical Environment Studies and Geography, James loads (Orth & Moore, 1983;Cambridge & McComb, 1984;Walker & McComb, 1992), increasing attention has been devoted to understanding the ecology and physiology of these organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous application of DNA fingerprinting techniques to the seagrasses Posidonia australis from Australia and Zostera marina from California revealed low population genetic similarity. Alberte et al (1994) showed, using minisatellite analysis, (1) low within ( S, = 0.44 to 0.68) and between (Sb = 0.47 to 0.51) population similarities in geographically disjunct populations of Z, marina, (2) Australia (Waycott 1995), and more recently, a short report indicated some polymorphism in P. oceanica along the Thyrrenean coast of Italy (Franconi et al 1995). From our analysis, the genetic structure of Posidonia oceanica in the Western Mediterranean appears to be quite different from that observed in these previous studies on seagrasses.…”
Section: Results Discussionmentioning
confidence: 99%